2014
DOI: 10.3389/fncel.2014.00332
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic α7 receptor activation selectively potentiates the function of NMDA receptors in glutamatergic terminals of the nucleus accumbens

Abstract: We here provide functional and immunocytochemical evidence supporting the co-localization and functional interaction between nicotinic acetylcholine receptors (nAChRs) and N-methyl-D-aspartic acid receptors (NMDARs) in glutamatergic terminals of the nucleus accumbens (NAc). Immunocytochemical studies showed that a significant percentage of NAc terminals were glutamatergic and possessed GluN1 and α7-containing nAChR. A short-term pre-exposure of synaptosomes to nicotine (30 µM) or choline (1 mM) caused a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
(57 reference statements)
2
34
0
Order By: Relevance
“…The most abundant nAChRs expressed by hippocampal astrocytes in C57Bl/6 mice are α4β2- and α4β4-nAChRs (Gahring et al, 2004) but Carba still caused a full saturation of NMDARs in the presence the α4β4- and α4β2-nAChR antagonist DHβE (P = 0.889). In contrast, we found that the effect of Carba was prevented by the α7nAChR antagonist MLA (Figure 5A, P < 10 −9 ), in line with observations that α7nAChR activation promotes NMDAR activity (Lin et al, 2013; Yang et al, 2013; Zappettini et al, 2014) and favors D-serine release (Singh et al, 2013). As expected from this finding, the α7nAChR selective agonist AR-R17779 (AR-R) alone elicited a full saturation of NMDARs (P < 10 −8 vs control), which was attenuated by the co-application of MLA (P < 10 −4 vs AR-R).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The most abundant nAChRs expressed by hippocampal astrocytes in C57Bl/6 mice are α4β2- and α4β4-nAChRs (Gahring et al, 2004) but Carba still caused a full saturation of NMDARs in the presence the α4β4- and α4β2-nAChR antagonist DHβE (P = 0.889). In contrast, we found that the effect of Carba was prevented by the α7nAChR antagonist MLA (Figure 5A, P < 10 −9 ), in line with observations that α7nAChR activation promotes NMDAR activity (Lin et al, 2013; Yang et al, 2013; Zappettini et al, 2014) and favors D-serine release (Singh et al, 2013). As expected from this finding, the α7nAChR selective agonist AR-R17779 (AR-R) alone elicited a full saturation of NMDARs (P < 10 −8 vs control), which was attenuated by the co-application of MLA (P < 10 −4 vs AR-R).…”
Section: Resultssupporting
confidence: 89%
“…In addition to being tightly correlated with vigilance states (Lee et al, 2005; Marrosu et al, 1995; Zant et al, 2016), cholinergic signaling potentiates NMDAR activity and modulates NMDAR-dependent functions (Kirkwood et al, 1999; Lin et al, 2013; Markram and Segal, 1990; Yang et al, 2013; Zappettini et al, 2014). ACh also elicits intracellular Ca 2+ signaling in astrocytes through muscarinic receptors (Takata et al, 2011), α4β2- and α4β4-nAChRs receptors (Gahring et al, 2004), or α7nAChRs (Sharma and Vijayaraghavan, 2001; Shen and Yakel, 2012) and can promote D-serine release or synthesis (Lin et al, 2013; Singh et al, 2013; Takata et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, nicotine has been reported to evoke internalization of presynaptic NMDA receptors in dopaminergic terminals of the rat nucleus accumbens resulting in decreased NMDA-induced dopamine release [147]. On the other hand, nicotine pretreatment increased the responses of the NMDA receptors, which contain the GluN2A subunits, via activation of α7-nACh receptor subtypes on the glutamatergic nerve endings of the nucleus accumbens [148].…”
Section: Modulation Of Nmda Receptors By Acetylcholinementioning
confidence: 93%
“…Acetylcholine (ACh) has been hypothesised to be necessary for top-down attentional modulation (Deco and Thiele, 2011). ACh affects synaptic transmission through NMDA receptors (FloresHernandez et al, 2009;Ishibashi et al, 2014;Zappettini et al, 2014;Salamone et al, 2014;Zhang et al, 2014) and may, therefore, be partially responsible for NMDA receptor dependent synaptic plasticity. Indeed, reinforcement learning has been proposed as a key component in the development of perceptual and more generally causal inference (Shams and Beierholm, 2010).…”
Section: Neuromodulationmentioning
confidence: 99%